Medium-Term Effects of a Train Derailment on the Physical and Psychological Health of Men - Maltais, Danielle (Am J Mens Health, 2019)
In July 2013, the derailment of a train caused the death of 47 people and the destruction of Lac-Mégantic’s downtown area (Canada). Three years after this event, a population survey was conducted among a representative sample of 800 adults, including 282 men. Several significant differences were observed among respondents of a survey based on their level of exposure to this tragedy, including their physical (changes in physical health) and psychological health (post-traumatic stress disorder, mood and anxiety disorders, psychological distress, signs of depression, consultation of social workers and psychologists) as well as their use of prescribed (anxiolytics and antidepressants) and nonprescribed drugs. Such results can be explained by the nature, magnitude, and cause of the event.